Hypoxic bradycardia: an enigma in coronavirus disease 2019 - Kapoor, Ruchi; R., Lakshmi; Devaraj, Ganga Dutt; Mohan, Aparna (International Journal of Research in Medical Sciences, 2022)
Coronavirus disease 2019 varies from asymptomatic to severe acute respiratory syndrome with multiple organ involvement, primarily involving the microvasculature and heart. Acute myocardial injury is the most frequently observed and reported cardiac complication with acute coronary events, acute left ventricular systolic dysfunction, and cardiac arrhythmias, but sinus bradycardia reported only in a few cases. The development of sinus bradycardia can be crucial warning sign of onset of severe cytokine storm. The primary determinant of severity of COVID-19 is aging and co-morbidities such as diabetes and hyperlipidemia with dysregulated immunological status. Patients with pre-existing cardiovascular disease infected with COVID-19 have increased risk of severity and mortality. Literature available regarding the occurrence of bradycardia is limited, and electrophysiology studies in COVID-19 patients have shown sinus bradycardia, heart block, bundle branch block, and intraventricular conduction delay. The pathophysiological mechanism regarding the occurrence of bradycardia is not yet known entirely. Cardiac manifestations could be attributed to multiple clinical etiologies, including direct viral myocardial damage, inflammatory response, hypoxia, hypotension, downregulation of angiotensin-converting enzyme 2 (ACE-2), drug toxicity, and endogenous toxicity of catecholamine adrenergic status, also severe hypoxic damage of lungs by COVID-19 can also act as a trigger. We report one such case of bradycardia due to COVID-19 detected through intensive monitoring and managed successfully in the ICU of tertiary care dedicated COVID-19 hospital. Bradycardia in COVID-19 is a rare clinical phenomenon, could be a worst prognostic marker. If detected early may help in prognostication and, if managed appropriately, will avert a life-threatening complication.